2020
DOI: 10.3390/app10124254
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Spatio-Temporal Drought Forecasting Using Random Forests Model at New South Wales, Australia

Abstract: Droughts can cause significant damage to agriculture and water resources, leading to severe economic losses and loss of life. One of the most important aspect is to develop effective tools to forecast drought events that could be helpful in mitigation strategies. The understanding of droughts has become more challenging because of the effect of climate change, urbanization and water management; therefore, the present study aims to forecast droughts by determining an appropriate index and analyzing its changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…This outcome is consistent with the findings presented by [119], that the accuracy of the prediction process is greater for long-term drought episodes compared to the short-term periods. Further, our finding is in agreement with the study of SPEI prediction in New South Wales (Australia) which concluded that RF achieved RMSE and R 2 results of 0.53 and 0.76, respectively, for SPEI-3 [120]. In contrast, the SVM algorithm applied to Combined Terrestrial Evapotranspiration Index (CTEI) resulted in an R 2 value of 0.82 and the lowest errors in terms of the root mean squared error (RMSE) (0.33) and Mean Absolute Error (MAE) (0.20) in the Ganga River basin [42] which agree with our results, and were much better in comparison to the other ML models they applied.…”
Section: B Evaluation Of the Machine Learning Modelssupporting
confidence: 92%
“…This outcome is consistent with the findings presented by [119], that the accuracy of the prediction process is greater for long-term drought episodes compared to the short-term periods. Further, our finding is in agreement with the study of SPEI prediction in New South Wales (Australia) which concluded that RF achieved RMSE and R 2 results of 0.53 and 0.76, respectively, for SPEI-3 [120]. In contrast, the SVM algorithm applied to Combined Terrestrial Evapotranspiration Index (CTEI) resulted in an R 2 value of 0.82 and the lowest errors in terms of the root mean squared error (RMSE) (0.33) and Mean Absolute Error (MAE) (0.20) in the Ganga River basin [42] which agree with our results, and were much better in comparison to the other ML models they applied.…”
Section: B Evaluation Of the Machine Learning Modelssupporting
confidence: 92%
“…The "no trend" in precipitation with time is assumed in the null hypothesis (H o ) of the test and vice versa for the alternative hypothesis (H a ). The Equations (9)- (12) show the test stats T of the MK test.…”
Section: Mann-kendall Test (Mk Test)mentioning
confidence: 99%
“…Simulation results from general circulation models (GCMs) are used to study the implications of hydro-climatic change and are considered the most comprehensive and valid instruments, with the ability to reproduce climate variables in chronological order as well as yield future projections using scenarios [8][9][10][11] recommended by the intergovernmental panel on climate change (IPCC). Numerous outputs from GCMs are available to gain insight into climate processes and the impact of various scenarios on these processes [12,13]. The question arises as to how to use these climate simulations to obtain meteorological inputs for impact models to characterize all the uncertainties involved in the models.…”
Section: Introductionmentioning
confidence: 99%
“…Four types of droughts are found in the literature: meteorological, agricultural, hydrological, and socio-economic (Sharafati et al 2019;Nabaei et al 2019;Deng et al 2018). Australia is frequently affected by agricultural drought events (Rahmati et al 2019;Dikshit et al 2020b).…”
Section: Introductionmentioning
confidence: 99%